Elimination of residual aliasing artifact that resembles brain lesion on multi‐oblique diffusion‐weighted echo‐planar imaging with parallel imaging using virtual coil acquisition. Issue 5 (30th October 2019) - Liu, Xiaoxi; Hui, Edward S.; Chang, Hing‐Chiu
Abstract : Background: Single‐shot diffusion‐weighted echo‐planar imaging (ssDW‐EPI) acquired with parallel imaging and a multi‐oblique scan plane may suffer from residual aliasing artifacts, resembling lesions on the calculated apparent diffusion coefficient (ADC) map. Purpose: To combine ssDW‐EPI and virtual coil acquisition and develop a self‐reference reconstruction method to eliminate the residual aliasing artifact on multi‐oblique ssDW‐EPI sequence with parallel imaging and multiple signal averaging. Study Type: Prospective. Subjects: Three healthy subjects and 50 stroke patients. Field Strength/Sequence: Conventional ssDW‐EPI with parallel imaging, and proposed ssDW‐EPI with virtual coil acquisition at 1.5T. Assessment: The efficacy of the proposed method was evaluated in 50 stroke patients by comparing the ssDW‐EPI with conventional parallel imaging reconstructions. The extent of residual aliasing artifacts were rated on a 5‐point Likert scale by three independent raters. Only the data without residual aliasing artifacts on conventional ssDW‐EPI were included for the assessment of signal‐to‐noise ratio (SNR), ghost‐to‐signal ratio (GSR), and ADC. Statistical Tests: The interobserver agreements for examining residual aliasing artifacts were measured by the intraclass correlation coefficient (ICC). A two‐sample t ‐test was performed for comparing SNR, GSR, and ADC. Results: There was a perfect agreement (ICC = 1.00) in the examination of residual aliasing artifacts on images obtained using the proposed method. The incidence rates of the residual aliasing artifact on the ADC maps obtained from the scanner console and proposed method were 60% (ie, 30 out of 50) and 0%, respectively. The proposed method offers significantly lower GSR than conventional parallel imaging reconstruction ( P < 0.001). There was no significant difference in SNR ( P = 0.20–0.51) and ADC values ( P = 0.20–0.94) between conventional parallel imaging reconstructions and the proposed method. Data Conclusion: It appears that our method could effectively eliminate artifacts and significantly improve the GSR of b = 0 T2 WI and b > 0 DWI, as well as permit ADC measurement consistent with conventional techniques. Our method may be beneficial to clinical assessment of the brain that utilizes multi‐oblique ssDW‐EPI. Level of Evidence: 1 Technical Efficacy Stage: 1 J. Magn. Reson. Imaging 2020;51:1442–1453.